GOVERNMENT SPENDING (ECONOMY, SOCIAL PROTECTION, HEALTH, EDUCATION) ON INCOME INEQUALITY IN WEST JAVA - Prannisa, Alfath; Muljarijadi, Bagdja; Wardhana, Adhitya (Faculty of Economics and Business, University of Pasundan, 2023)
This study aims to examine the effect of government spending on the economy, social protection, health, and education on income inequality in West Java during 2015-2020. Income inequality in this study uses the Gini ratio. The estimation uses a fixed effect panel data model using the cross-section weight (EGLS) method. The results show that government spending contributes to reducing income inequality in West Java in 2015-2020. Meanwhile, control variables such as GRDP per capita and poverty have a significant effect on increasing income inequality and investment variables have a significant effect on reducing income inequality.